Karakteristik Pengeringan Rempah Daun Menggunakan Fluidized Bed Drier dan Tray Drier - Tjahja Muhandri; Fahim Muchammad Taqi; Subarna Subarna; Dian Widiawati (Perhimpunan Ahli Teknologi Pangan Indonesia bekerjasama dengan Departemen Ilmu dan Teknologi Pangan, IPB University Bogor, Indonesia, 2023)
Bay leaves (Sygygium polyanthum), kaffir lime leaves (Citrus hystrix) and pandan leaves (Pandanus amaryllifolius) are herb leaves with unique aroma that are often added to dishes to strengthen and enrich the taste. The high demand of the leaves has prompted efforts to make them easy to distribute and shelf stable. Drying can increase the shelf life of these leaves with acceptable quality. The objectives of the research were to determine drying models for these leaves using two types of driers and to determine the panelist's preference for the dried and rehydrated leaves. These herb leaves are fresh-picked from the tree, cleaned and dried using the two different driers, i.e. fluidized bed drier (temperature 40-42°C) and tray drier (temperature 58-61°C). The leaves were weighed every 15 minutes until they reached a constant weight. Fresh leaves and dry leaves were photographed. The drying kinetics of both types of driers were checked with the Lewis model and Page model. Panelist preference test was carried out on dry leaves and leaves that had been rehydrated using hot water. The results showed that drying with a tray drier was able to dry faster than that with a fluidized bed drier. The Page drying model is more suitable to describe the drying conditions than the Lewis drying model. Panelists preferred dry and rehydrated herb leaves obtained from fluidized bed drying.